Determination of the ash content of coal without ashing: a simple technique using laser-induced breakdown spectroscopy - Haider, A F M Yusuf; Rony, M. A.; Abedin, K. M. (© 2013 American Chemical Society, 2017)
This article was published in the Journal Energy and Fuels [© 2013 American Chemical Society] and the definite version is available at : 10.1021/ef400566u